Legal and Organizational Issues of the Administrative Activities of the Police in Counteracting Extremism - Yuritsin, Andrey E. (Sibirskoe ûridičeskoe obozrenie (Online), 2016)
The article considers legal and organizational problems of administrative activity of the Russian police in counteracting extremism. The author analyzes the legal framework of police activity to curb extremism, defines the place of the Interior agencies in the system of the state bodies engaged in combating extremism, investigates organizational issues of administrative activities of the police in combating extremism. On the basis of the conducted research the author gives his proposals on improving activities of the police in combating extremism.